Analisis Yuridis Kewenangan Lembaga Manajemen Kolektif Nasional (LMKN) terhadap Distribusi Royalti dalam Perspektif Kepastian Hukum - Dudung Hidayat (Jurnal Hukum Lex Generalis, 2026)
The increasing use of songs and/or music in commercial activities due to the development of digital technology has raised legal questions regarding the protection of creators’ economic rights, particularly in relation to the collection and distribution of royalties. In practice, several problems remain, including lack of transparency, delays in payment and insufficient supervision, which result in legal uncertainty for creators. Based on Law Number 28 of 2014 concerning Copyright, the National Collective Management Organization (LMKN) has the function of collecting and distributing royalties. This study aims to identify the legality of the National Collective Management Organization (LMKN) in relation to royalty distribution from the perspective of legal certainty. The research method used in this study is qualitative research with a normative juridical approach, conducted through the examination of primary, secondary and tertiary legal materials. The results of the study show that although the authority of LMKN has a strong legal basis, its implementation has not been optimal in providing legal certainty. Therefore, regulatory strengthening, increased transparency and the development of a more accountable royalty management system are needed to ensure the fair and sustainable fulfillment of creators’ economic rights.